Bismuth subsalicylate, probiotics, rifaximin and vaccines for the prevention of travelers’ diarrhea: a systematic review and network meta-analysis - Fan, Hao; Liu, I-Chun; Gao, Lei; Wu, Lanka (Frontiers in Pharmacology, 2024)
Background: Bismuth subsalicylate (BSS), probiotics, rifaximin, and vaccines have been proposed as preventive modalities for patients with travelers' diarrhea (TD), but their comparative effectiveness for prevention has rarely been studied. We aimed to perform a systematic review and network meta-analysis to test whether one of these modalities is more effective than the others in reducing the incidence of TD.We searched Pubmed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and clinical registries from inception of the databases through November 18, 2023, without language restriction, for randomized controlled trials (RCTs) evaluating the efficacy of BSS, probiotics, rifaximin, and vaccines in preventing TD. The primary outcome was the incidence of TD and the safety outcome was the incidence of adverse events. The relative ratio (RR) was used to assess the effect of the modalities, and RR estimates between any two of the modalities were calculated and pooled using a frequentist network meta-analysis model.Thirty-one studies (recruiting 10,879 participants) were included in the analysis.Sixteen were judged to have a low risk of bias. In the aggregate analysis, BSS and rifaximin were more effective than placebo and other treatment modalities, which was further confirmed in the individual analysis. The comparison between rifaximin and placebo achieved high confidence, while the comparisons between BSS and placebo, ETEC and probiotics, and rifaximin and vaccines achieved moderate confidence. BSS had a higher rate of adverse events compared with other treatments.Conclusions: Rifaximin had a relative lower TD incidence and lower adverse event rate, and the evidence was with moderate confidence.